What's this you're reading? Book - Media - Knowledge - during Middle Ages and Early Modern Times (KULT_online, 2014)
The materiality and mediality of books as knowledge carriers changed fundamentally at the passage from Middle Ages to Early Modern Times. But did the invention of book printing immediately alter the media 'book'? Surprisingly not. Which meaning and function, then, do manuscripts or printed books have over the course of time? A book could be…what? A sign, an experiment, a collector's item, a knowledge collector, a digital copy. It can popularize, convey, obscure. The anthology Buchkultur und Wissensvermittlung in Mittelalter und Früher Neuzeit shows clearly many different approaches to the research topic 'book'.